PHARMACEUTICAL LOGISTICS AS A NEW PARADIGM IN THE SYSTEM OF SPECIALIZED PHARMACEUTICAL CARE FOR CANCER PATIENTS - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Филимонов, Сергей Николаевич; Захаров, Вадим Николаевич; Вайман, Евгений Федорович; Семенихин, Виктор Андреевич (Medicine in Kuzbass, 2024)
In modern conditions, the study of the drug supply system for cancer patients is carried out to develop a conceptual model for improving specialized pharmaceutical care and the general principles of its implementation. Economic realities require supplementing the existing paradigm of clinical thinking with elements that ensure the rationality of choosing possible treatment options for patients with cancer. In these conditions, the usual «efficiency – safety» coordinate system is not enough. The inclusion of the concept of pharmaceutical logistics in the pharmaceutical lexicon is an urgent need.